2022
DOI: 10.1002/ange.202200413
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Engineered Covalent Organic Frameworks for Hydrogen Peroxide Photosynthesis

Abstract: Synthesizing H2O2 from water and air via a photocatalytic approach is ideal for efficient production of this chemical at small‐scale. However, the poor activity and selectivity of the 2 e− water oxidation reaction (WOR) greatly restricts the efficiency of photocatalytic H2O2 production. Herein we prepare a bipyridine‐based covalent organic framework photocatalyst (denoted as COF‐TfpBpy) for H2O2 production from water and air. The solar‐to‐chemical conversion (SCC) efficiency at 298 K and 333 K is 0.57 % and 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Covalent organic frameworks (COFs) are another new type of emerging metal-free photocatalysts due to their well-defined pore structure, extended light-response range, and highly tunable optoelectronic property. Although several pioneering studies have shown that COFs could be endowed with promising photocatalytic H 2 O 2 production efficiency through molecular tailoring, topology tuning, mass transfer regulating, Lewis acid site manipulating, and biocatalytic approach mimicking, several critical issues need to be addressed before their practical implementation. First, the imine bonds are susceptible to harsh conditions, as a majority of the highly crystalline COFs were prepared using the reversible Schiff-base chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Covalent organic frameworks (COFs) are another new type of emerging metal-free photocatalysts due to their well-defined pore structure, extended light-response range, and highly tunable optoelectronic property. Although several pioneering studies have shown that COFs could be endowed with promising photocatalytic H 2 O 2 production efficiency through molecular tailoring, topology tuning, mass transfer regulating, Lewis acid site manipulating, and biocatalytic approach mimicking, several critical issues need to be addressed before their practical implementation. First, the imine bonds are susceptible to harsh conditions, as a majority of the highly crystalline COFs were prepared using the reversible Schiff-base chemistry.…”
Section: Introductionmentioning
confidence: 99%